2014
DOI: 10.1007/s10096-014-2164-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of female genital tuberculosis among infertile women: a study from a tertiary maternal health care research centre in South India

Abstract: The purpose of this investigation was to estimate the proportion of female genital tuberculosis (FGTB) among infertile women, along with the mean cost of diagnosis by different methods. The study was carried out on 211,335 women, of which 31,755 (15.02 %) were infertile. 202 women were highly suspected of FGTB on laparoscopy, which was later ascertained by multi-gene polymerase chain reaction (PCR), and the cost was estimated. The majority of the patients were infertile (77.23 %), with menstrual disturbances (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
1
23
0
2
Order By: Relevance
“…Liu et al reported a similar case in which untreated prior pulmonary TB developed into miliary TB during pregnancy [11]. Genital TB (GTB) is a form of extrapulmonary TB and a major cause of primary infertility among women in TB-endemic countries [24], with a prevalence rate of 28.4% in our hospital, as observed in previous studies [25,26]. GTB may cause fallopian tube obstruction, reduced endometrial receptivity, and ovarian dysfunction, leading to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported a similar case in which untreated prior pulmonary TB developed into miliary TB during pregnancy [11]. Genital TB (GTB) is a form of extrapulmonary TB and a major cause of primary infertility among women in TB-endemic countries [24], with a prevalence rate of 28.4% in our hospital, as observed in previous studies [25,26]. GTB may cause fallopian tube obstruction, reduced endometrial receptivity, and ovarian dysfunction, leading to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported a similar case in which untreated prior pulmonary TB developed into miliary TB during pregnancy [18]. Genital TB (GTB) is a form of extrapulmonary TB and a major cause of primary infertility among women in TB-endemic countries [32], with a prevalence rate of 28.4% in our hospital, as observed in previous studies [33,34]. GTB may cause fallopian tube obstruction, reduced endometrial receptivity, and ovarian dysfunction, leading to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Dans une Ă©tude indienne rĂ©cemment publiĂ©e colligeant plus de 30000 femmes stĂ©riles, l'Ă©tiologie tuberculeuse a Ă©tĂ© retrouvĂ©e dans 15% des cas [ 12 ], ce qui justifie la recherche systĂ©matique d'une TG chez toute femme stĂ©rile. Les troubles du cycle Ă  type d'amĂ©norrhĂ©e primaire ou secondaire sont un autre motif de consultation, retrouvĂ©s dans 5 Ă  20% des cas [ 13 ].…”
Section: Discussionunclassified
“…Les techniques d'amplification nuclĂ©ique ont considĂ©rablement facilitĂ© le diagnostic de certaines formes de tuberculose extrapulmonaire. La dĂ©termination rapide de la prĂ©sence du gĂ©nome bactĂ©rien par polymerase chain reaction (PCR) constitue actuellement un progrès rĂ©cent dans le diagnostic de la TG [ 12 , 20 ], avec une spĂ©cificitĂ© et une sensibilitĂ© dĂ©passant les 60% dans certaines Ă©tudes [ 21 ]. L'examen histologique d'une biopsie de l'endomètre, de lĂ©sion pĂ©ritonĂ©ale ou de masse tubo-ovarienne reste l'examen clĂ© pour confirmer le diagnostic, tout en sachant que la nĂ©crose casĂ©euse peut manquer dans d'authentiques tuberculoses.…”
Section: Discussionunclassified